Comparative analysis of newly introduced disinfectants in hospitals in India: An important aspect of infection control policy - Banerjee, Tuhina; Filgona, Joel; Anupurba, Shampa (International Journal of Infection Control, 2013)
The effective use of disinfectants constitutes an important factor in preventing hospital acquired infections. This study was undertaken to compare the effects of three newly introduced disinfectants in a number of tertiary care hospitals in India, namely superoxidized water (SOW) and two quaternary ammonium compounds (QACs), against the effects of 70% alcohol as one of the most commonly used disinfectants. All the disinfectants were tested for their effectiveness against multidrug resistant (MDR) Pseudomonas spp, methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant enterococci (VRE). A serial tenfold dilution of the bacterial suspensions were made and subjected to the action of different disinfectants for different length of time and in presence and absence of organic matter. Reduction in colony count was noted by semiquantitative colony count method. Results were expressed as percentage reductions and analyzed statistically. SOW showed good activity against most of the isolates, except against MRSA in presence of organic matter, where QACs were better. The most persistent effect was seen with SOW among all the disinfectants tested. The disinfectants varied in their effects towards different organisms in different environmental conditions. Therefore, disinfection policies should take into consideration the type of ward and surfaces to be disinfected along with reasons for disinfection for an effective step towards infection control.Key words: SOW; QACs; disinfectants; comparison